Antagonistic Effect of Sucrose Availability and Auxin on Rosa Axillary Bud Metabolism and Signaling, Based on the Transcriptomics and Metabolomics Analysis - Wang, Ming; Ogé, Laurent; Pérez Garcia, Maria-Dolores; Launay-Avon, Alexandra; Clément, Gilles; Le Gourrierec, Jose; Hamama, Latifa; Sakr, Soulaiman (Frontiers in Plant Science, 2022)
Shoot branching is crucial for successful plant development and plant response to environmental factors. Extensive investigations have revealed the involvement of an intricate regulatory network including hormones and sugars. Recent studies have demonstrated that two major systemic regulators – auxin and sugar – antagonistically regulate plant branching. However, little is known regarding the molecular mechanisms involved in this crosstalk. We carried out two complementary untargeted approaches – RNA-seq and metabolomics – on explant stem buds fed with different concentrations of auxin and sucrose resulting in dormant and non-dormant buds. Buds responded to the combined effect of auxin and sugar by massive reprogramming of the transcriptome and metabolome. The antagonistic effect of sucrose and auxin targeted several important physiological processes, including sink strength, the amino acid metabolism, the sulfate metabolism, ribosome biogenesis, the nucleic acid metabolism, and phytohormone signaling. Further experiments revealed a role of the TOR-kinase signaling pathway in bud outgrowth through at least downregulation of Rosa hybrida BRANCHED1 (RhBRC1). These new findings represent a cornerstone to further investigate the diverse molecular mechanisms that drive the integration of endogenous factors during shoot branching.